User satisfaction in relation to Primary Health Care services in Brazil - Cantalino,Juliana Leal Ribeiro (2021)
ABSTRACT OBJECTIVE: To analyze user satisfaction in relation to access, infrastructure and quality of Primary Health Care (PHC) services in Brazil. METHODS: This cross-sectional study was conducted with data from 114,615 users linked to 30,523 health teams, obtained through the database of the Programa Nacional de Melhoria do Acesso e da Qualidade da Atenção Básica (PMAQ-AB —National Program for the Improvement of Access and Quality of Primary Care). Independent variables related to access, infrastructure and quality of services in PHC were studied. The outcome, user satisfaction, was measured using the variables: “if given the option, I would change the staff or health service” and “I would recommend this health service to a friend or family member.” To assess satisfaction according to independent exposure variables, Pearson’s chi-squared test was used, considering a significance level of 5%. Descriptive analyses of the variables were performed using absolute (n) and relative (%) frequencies. RESULTS: User satisfaction was associated with the variables of access (p < 0.001), infrastructure (p < 0.001) and quality of services (p < 0.001) in PHC. The proximity of the service, attention to spontaneous demand, listening and the respect of professionals to the singularities of the patient, as well as the problem-solving capacity of the services, without the need for referrals to others and the good infrastructure, were related to user satisfaction. CONCLUSION: To ensure the improvement of the quality of services offered in PHC in Brazil, the aspects of user satisfaction identified in this study should be considered in the organization and management of services.